An unusual side effect of topical corticosteroids. - Rebelo Lima, J.; Aldeia da Silva, R.; Teixeira, J.; Raposo, F. (European Journal of Pediatric Dermatology, 2025)
We present a case of a 23-day-old newborn that was brought to the emergency department due to a well delimited, circular pale area around the umbilicus after 3 days of treatment with topical betamethasone valerate for a purulent discharge from the umbilical stump. The most likely diagnosis was an adverse drug reaction (ADR) to the topical corticosteroid (TC), specifically vasoconstriction. Complete resolution was observed after discontinuation of the drug in question. Although uncommon in the neonatal period, the phenomenon of skin pallor caused by vasoconstriction is a described ADR of TC (1). It is a reversible condition (as demonstrated in this case), and management involves reassuring the family and discontinuing the treatment.